2019
DOI: 10.1039/c8ra09841g
|View full text |Cite
|
Sign up to set email alerts
|

Efficient degradation of organic pollutants by peroxymonosulfate activated with MgCuFe-layered double hydroxide

Abstract: MgCuFe-layered double hydroxide exhibited high catalytic activity to activate peroxymonosulfate for degradation of organic pollutants. SO4˙− and ·OH are the main reactive radicals involved in the degradation of organic pollutants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(16 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Advanced oxidation processes (AOPs) for the remediation of contaminated soils, groundwater, and sediments have received considerable attention in recent years. [1][2][3] These processes are based mostly on activation of hydrogen peroxide (H 2 O 2 ), 4 titanium dioxide (TiO 2 ), 5 persulfate (PDS) 6,7 and peroxymonosulfate (PMS) [8][9][10] to generate oxidizing species such as sulfate radical (SO 4 c À ) (2.5-3.1 V) and hydroxyl radicals (cOH) (1.9-2.7 V), 11 which are highly reactive oxidants toward organic compounds. Among AOPs, PMS has emerged as a popular technique in environmental remediation.…”
Section: Introductionmentioning
confidence: 99%
“…Advanced oxidation processes (AOPs) for the remediation of contaminated soils, groundwater, and sediments have received considerable attention in recent years. [1][2][3] These processes are based mostly on activation of hydrogen peroxide (H 2 O 2 ), 4 titanium dioxide (TiO 2 ), 5 persulfate (PDS) 6,7 and peroxymonosulfate (PMS) [8][9][10] to generate oxidizing species such as sulfate radical (SO 4 c À ) (2.5-3.1 V) and hydroxyl radicals (cOH) (1.9-2.7 V), 11 which are highly reactive oxidants toward organic compounds. Among AOPs, PMS has emerged as a popular technique in environmental remediation.…”
Section: Introductionmentioning
confidence: 99%
“…The unique layered structure of LDH combined with its tuneable controllability of metal ions and structural stability made these materials promising for water splitting, energy storage and environmental remediation. [19][20][21] Herein, a novel core@shell Fe 3 O 4 @CoFe-LDH was synthesized and applied for PMS activation in azo-dye AO7 degradation. The nanocomposite was prepared via a simple co-precipitation method and characterized by various analytical methods.…”
Section: Introductionsmentioning
confidence: 99%
“…The unique layered structure of LDH combined with its tuneable controllability of metal ions and structural stability made these materials promising for water splitting, energy storage and environmental remediation. 19–21 For instance, Guo et al successfully synthesized CoCu-LDH composites with great performance in PMS activation for removal of lomefloxacin. 22 Zhao et al reported that CoMn-LDH/PMS system achieved 52.2% TOC removal rate of acid orange G. 23 Hence, cobalt-based LDH catalysts look efficient for the activation of PMS.…”
Section: Introductionsmentioning
confidence: 99%
“…Analyzing these peaks, the REELS has generated complementary results to XPS in Figure b, where the peak at 946.63 eV can be correlated with the precursor concentration, the x = 0.00–0.10 value of bismuth. These peaks are commonly observed as satellite peaks for atoms in ferrite based alloys …”
mentioning
confidence: 98%
“…These peaks are commonly observed as satellite peaks for atoms in ferrite based alloys. 40 To study the effect of polarized light, we investigate differential absorption of left and right circular polarized light using magnetic circular dichroism (MCD); see Figure 4b. Here we observe that the shapes of the MCD spectra for all the samples are similar (less than 10% variation in the peak locations), except for sample 2 (x = 0.02), which has a large deviation in its MCD properties.…”
mentioning
confidence: 99%